Brain metastasis from gastrointestinal cancers: a systematic review - Esmaeilzadeh, Majid; Hafezi, Mohammadreza; Mehrabi, Arianeb (The international journal of clinical practice, 2014)
Background: Brain metastases (BM) from the gastrointestinal tract (GIT) cancers are relatively rare. Despite those advances in diagnostic and treatment options, life expectancy and quality of life in these patients are still poor. In this review, we present an overview of the studies which have been previously performed as well as a comprehensive strategy for the assessment and treatment of BM from the GIT cancers. Method: To obtain information on brain metastases from GIT, we performed a systematic review of Medline, EMBASE and the Cochrane Central Register of Controlled Trials (CENTRAL). The collected data included patient characteristics, primary tumor data and brain metastases data. Result: In our search of the literature, we found 74 studies between 1980 and 2011, which included 2538 patients with brain metastases originated from gastrointestinal cancer. Analysis of available data showed that among 2538 patients who had brain metastases from GIT, a total of 116 patients (4.57%) had esophageal cancer, 148 patients (5.83%) had gastric cancer, 233 patients (9.18%) had liver cancer, 13 patients had pancreas cancer (0.52%) and 2028 patients (79.90%) had colorectal cancer. The total median age of the patients was 58.9 years. Conclusion: Brain metastases have been considered the most common structural neurological complication of systemic cancer. Due to poor prognosis they influence the survival rate as well as the quality of life of the patients. The treatment of cerebral metastasis depends on the patients' situation and the decisions of the treating physicians. The early awareness of a probable metastasis from GI to the brain will have a great influence on treatment outcomes as well as the survival rate and the quality-of-life of the patients.
Gesehen am 29.09.2020